2019
DOI: 10.1093/jas/skz208
|View full text |Cite
|
Sign up to set email alerts
|

BOARD INVITED REVIEW: The pig microbiota and the potential for harnessing the power of the microbiome to improve growth and health1

Abstract: A variety of microorganisms inhabit the gastrointestinal tract of animals including bacteria, archaea, fungi, protozoa, and viruses. Pioneers in gut microbiology have stressed the critical importance of diet:microbe interactions and how these interactions may contribute to health status. As scientists have overcome the limitations of culture-based microbiology, the importance of these interactions has become more clear even to the extent that the gut microbiota has emerged as an important immunologic and metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 138 publications
2
36
0
1
Order By: Relevance
“…The role of intestinal microbiota in host physiological health has been recognized [38,39], and pioneers in gut microbiology have emphasized the significance of diet: the microbe interactions may contribute to health status [40]. In this study, Clostridia were abundant in sows from the control group, and Clostridial flagella were known to exert a peculiar role in adhesion and pathogenicity [41].…”
Section: Discussionmentioning
confidence: 87%
“…The role of intestinal microbiota in host physiological health has been recognized [38,39], and pioneers in gut microbiology have emphasized the significance of diet: the microbe interactions may contribute to health status [40]. In this study, Clostridia were abundant in sows from the control group, and Clostridial flagella were known to exert a peculiar role in adhesion and pathogenicity [41].…”
Section: Discussionmentioning
confidence: 87%
“…An optimal GM composition is able to maintain an equilibrium despite gastrointestinal challenges such as bacterial pathogens or parasites, which otherwise would result in a rapid population shift (Pluske et al, 2018). Diet is one of the major factors affecting microbial composition, and alterations in macronutrients will affect the composition (Aluthge et al, 2019). Additionally, prebiotics such as inulin with perceived health benefits have the potential to directly alter the microbiota through proliferation of the already resident beneficial bacteria (Nowland et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, ignoring the crosstalk between bacterial and protist communities, but also the contribution of gene-by-gene interactions shaping the pig gut microbial ecosystem. In their review, Aluthge et al (2019) [ 12 ] identified the lack of sophisticated computational and bioinformatics approaches as the major bottleneck to look beyond compositional changes and instead understand the functional causative role of the pig gut microbiome.…”
Section: Introductionmentioning
confidence: 99%